Liberal socialism : an alternative social ideal grounded in Rawls and Marx - Hunt, Ian. (Lanham, Maryland : Lexington Books, 2015)
Liberal Socialism exposes false ideas of justice behind neo-liberal capitalism and combines Rawls' ideas on justice and Marx's views on capitalism to make a plausible case for the alternative social ideal of liberal socialism. A fixed social structure gives equal weight to all competing claims for rights, liberties, and shares of the burdens and benefits of social cooperation, while allowing a democratic majority vote for liberal socialism.
Includes bibliographical references (pages 169-176) and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
English.
eBooks on EBSCOhost
Keywords: Rawls, John, -- 1921-2002.; Marx, Karl, -- 1818-1883.; Marx, Karl, -- 1818-1883; Rawls, John, -- 1921-2002; Socialism -- Philosophy; Social justice -- Philosophy; Justice sociale -- Philosophie; POLITICAL SCIENCE -- Political Ideologies -- Communism & Socialism; Social justice -- Philosophy; Socialism -- Philosophy